Jaundice outbreak likely caused by HEV in Amritsar, Punjab, India, 2013 - Tripurari Kumar; Aakash Shrivastava; Deepak Bhatia; Yash Mitra; Anil Kumar; Sharmeen Hussain; Lakhbir Singh Chauhan; Kayla F. Laserson; Jai Prakash Narain; Rajesh Kumar; Averhoff Francisco (BMC, 2019)
Abstract Background Hepatitis-E Virus (HEV) infection is endemic in Punjab, India. On 4th April 2013, public officials of Labour Colony, Amritsar reported > 20 jaundice cases occurring within several days. Methods We performed a case-control study to identify the cause and prevent additional cases of jaundice cases in Amritsar, Punjab, India in 2013. Results A total of 159 cases (attack rate 3.6%) and 1 death were identified in Labour and 5 adjoining colonies from January 1 to June 5, 2013. Persons with jaundice were more likely to report foul-smelling piped water (adjusted odds ratio [AOR], 4.0, 95% confidence interval [CI], 2.2-7.2) and used piped water for drinking (AOR, 5.1; 95% CI, 2.2-11.4) than persons without jaundice. Among 14 cases tested, all had anti-hepatitis E virus IgM, and none had anti-hepatitis A virus IgM. Additionally, 21/23 tap water samples from affected households had detectable fecal coliforms. An environmental investigation found that water pipelines were damaged during sewer construction and likely led to contamination of drinking water with hepatitis E virus. Conclusions Hepatitis E outbreaks are common in India, to curb future outbreaks of hepatitis E; measures to ensure safe drinking water are urgently needed.